MATE CONFLICT AND MALE-BEHAVIOR IN A SOLITARY WASP, TRYPOXYLON (TRYPARGILUM) POLITUM (HYMENOPTERA, SPHECIDAE) - Brockmann, H; Grafen, A (1989)
Among Hymenoptera there is an evolutionary or genetical conflict of interest between males and females over the sex of their offspring. Since males develop from unfertilized eggs, they are not related to their mates' sons. In most species there are few opportunities for males to interact with females, but in the pipe-organ mud-daubing wasp, Trypoxylon politum, and a few other species, males guard females' nests during provisioning. They chase away parasites and ants defend their position from conspecific males. Just prior to oviposition, males engage in an unusual sequence, repeatedly holding, pulling and copulating with the female. Despite the fact that males spend days sitting in nests, females lay large numbers of unfertilized, male eggs. The results suggest that males do not influence female sex-allocation decisions directly nor do they choose nests destined to contain daughters. However, females provide daughters with more food and a male guard may indirectly enhance the chance that the female will lay a fertilized egg through his effect on female provisioning efficiency. Comparisons with other species suggest that nest guarding evolved as a mating strategy and secondarily acquired a defensive function. © 1989.